APLIKASI PENJADWALAN UJIAN DAN KULIAH PENGGANTI DENGAN METODE ANT COLONY OPTIMIZATION (STUDI KASUS: FTI UNTAR) - Tandean, Vina; Hiryanto, Lely (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
An exam and substitute class application is made using Ant Colony Optimization algorithm. FTI Untar is used as a study case in this application development The purpose of using this algorithm is to get a schedule that not break constraints. The results of the tests done for the courses scheduling of odd semester of 2012 / 2013 until odd semester of 2013 / 2014, there is no hard-constraints (constraints that must be satisfied) violation, but there is a violation of soft constraint. It is also concluded that the average number of students who need to participate in more than one exam at the same time is 23 students. The number of students is an average sum of 5 subjects. After evaluating the existing schedule, it is concluded that the number of students who need to participate in more than one exam at the same time in the generated schedule is higher, but the violation of soft constraints is less. Key words Ant Colony Optimization,Exam, Substitute Class, University Timetabling Problem